Quality attributes for processing potato clones of purple-fleshed in Peru - Tirado Lara, Roberto; Tirado Malaver, Roberto Hugo (Revista de Ciências Agroveterinárias, 2019)
There is an increase in the demand and consumption of potato crisps and french chips in Peru. Therefore, the objective of the present work was to evaluate the industrial quality parameters of the physical and chemical characteristics of 17 advanced potato clones with purple pulp and select the clones with the best responses to the attributes of quality for industrial processing in Cajamarca, Peru. The results showed that the clones exhibited acceptable physical characteristics (tuber shape, depth of the eye, skin color, and color of the pulp) for processing, including the Amarilis variety. In addition, the clones reported tuber sizes within the recommended range for chips (40-60 mm) and french fries (≤ 45 mm). Clone CIP302306.19 produced the highest content of dry matter of the tuber (28.60%) and specific gravity (1,106 g cm-3), with low levels of reducing sugars (0.062%) and an acceptable range for the processing of the chips, while the lowest dry matter content (19.39%) and specific gravity (1.072 g cm-3), were reported by clone CIP302290.11. Most of the clones produced tubers with a dry matter content greater than 20% and a specific gravity greater than 0.080 g cm-3, in addition to low levels of reducing sugars, and they are within the acceptable range for chip processing. The study indicated that the tested clones could potentially be used for chip production because of their significant effects on processing parameters.